2011
DOI: 10.1093/hmg/ddr177
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the Akt/Gsk3-β signalling pathway is common to Drosophila expressing expanded untranslated CAG, CUG and AUUCU repeat RNAs

Abstract: Recent evidence supports a role for RNA as a common pathogenic agent in both the ‘polyglutamine’ and ‘untranslated’ dominant expanded repeat disorders. One feature of all repeat sequences currently associated with disease is their predicted ability to form a hairpin secondary structure at the RNA level. In order to investigate mechanisms by which hairpin-forming repeat RNAs could induce neurodegeneration, we have looked for alterations in gene transcript levels as hallmarks of the cellular response to toxic ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…This conclusion was made based on studies of two DM1 models: HSA LR mice, expressing CUG repeats in the 3′ UTR of skeletal muscle actin; and CHO double-stable clones expressing Tet-regulated pure CUG repeats. In agreement with our findings, a recent study has shown disruption of AKT/GSK3β signaling in neuronal cells in response to the expression of CUG repeats (40).…”
Section: Discussionsupporting
confidence: 94%
“…This conclusion was made based on studies of two DM1 models: HSA LR mice, expressing CUG repeats in the 3′ UTR of skeletal muscle actin; and CHO double-stable clones expressing Tet-regulated pure CUG repeats. In agreement with our findings, a recent study has shown disruption of AKT/GSK3β signaling in neuronal cells in response to the expression of CUG repeats (40).…”
Section: Discussionsupporting
confidence: 94%
“…Where expanded repeats are translated, they generally code for polyglutamine; however, the proteins in which they are located are all unrelated in the remainder of their amino-acid sequence. Therefore, much attention has been focused on expanded polyglutamine as the common basis of pathology (McLeod et al, 2005; van Eyk et al, 2011, 2012). Some of these diseases, however, have repeat expansions located within untranslated RNAs and/or arise from repeat sequences that cannot encode polyglutamine ( Figure 1 ; Richards, 2001; La Spada and Taylor, 2010).…”
Section: Is There a Common Pathogenic Agent?mentioning
confidence: 99%
“…(1) RNA sequestration – via alternative splicing (Mankodi et al, 2002; Ranum and Day, 2004) or Akt/GSK3β pathway (van Eyk et al, 2011; Jones et al, 2012; Lawlor et al, 2012). (2) RAN (repeat associated non-AUG) Translation (Zu et al, 2011; Ash et al, 2013; Mori et al, 2013; Todd et al, 2013).…”
Section: Mechanisms Of Rna-initiated Pathologymentioning
confidence: 99%
See 2 more Smart Citations